2016
DOI: 10.1186/s13287-016-0362-8
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regeneration in swine after cell injection and cell sheet transplantation of human dental pulp stem cells following good manufacturing practice

Abstract: BackgroundPeriodontitis, one of the most prevalent infectious diseases in humans, results in the destruction of tooth-supporting tissues. The purpose of the present study is to evaluate the effect of cell injection and cell sheet transplantation on periodontal regeneration in a swine model.MethodsIn the present study, human dental pulp stem cells (hDPSCs) were transplanted into a swine model for periodontal regeneration. Twelve miniature pigs were used to generate periodontitis with bone defects of 5 mm in wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0
14

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 50 publications
7
113
0
14
Order By: Relevance
“…Periodontal ligament cell sheets were used for periodontal regeneration in studies of dogs (Akizuki et al., ; Iwata et al., ). Besides PDLSCs (Ding, Liu, et al., ; Ding, Wang, et al., ; Liu et al., ), DPSCs (Hu et al., ; Khorsand et al., ), SHEDs (Fu, Jin, Ma, Fan, & Wang, ), BMMSCs (Du et al., ), ADSCs also have the potential for periodontal regeneration (Tobita & Mizuno, ).…”
Section: Periodontal Tissue Regenerationmentioning
confidence: 99%
“…Periodontal ligament cell sheets were used for periodontal regeneration in studies of dogs (Akizuki et al., ; Iwata et al., ). Besides PDLSCs (Ding, Liu, et al., ; Ding, Wang, et al., ; Liu et al., ), DPSCs (Hu et al., ; Khorsand et al., ), SHEDs (Fu, Jin, Ma, Fan, & Wang, ), BMMSCs (Du et al., ), ADSCs also have the potential for periodontal regeneration (Tobita & Mizuno, ).…”
Section: Periodontal Tissue Regenerationmentioning
confidence: 99%
“…Dental stem cell sheets have been shown to have advantages in odontogenic differentiation. [110][111][112] . However, which method is the most suitable for the neural differentiation of dental stem cells is still unclear.…”
Section: Future In S I G Hts and Mainly O B S Tacle Smentioning
confidence: 99%
“…A large amount of evidence has shown that stem cells, such as BMSCS and ADSCs, are available for tissue repair, including bone and muscle tissue, among others. Dental stem cell sheets have been shown to have advantages in odontogenic differentiation [110][111][112]. Dental stem cells possess greater promise over other sources of stem cells.…”
mentioning
confidence: 99%
“…Current 3D cell culture systems consist of either 3D cell sheet constructs (Hu et al., ; Iwata et al., ; Panduwawala et al., ), 3D biomaterials encapsulated with cells (Aizawa & Shoichet, ; Kraehenbuehl, Langer, & Ferreira, ), or cellular spheroids (Baraniak & McDevitt, ; Cheng et al., ). 3D multilayered cell sheets are stacked in layers.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is straightforward to hypothesize that PDL cells cultured in 3D superiorly maintain their stemness compared with a 2D culture system. Current 3D cell culture systems consist of either 3D cell sheet constructs (Hu et al, 2016;Iwata et al, 2015;Panduwawala et al, 2017), 3D biomaterials encapsulated with cells (Aizawa & Shoichet, 2012;Kraehenbuehl, Langer, & Ferreira, 2011), or cellular spheroids (Baraniak & McDevitt, 2012;Cheng et al, 2012). 3D multilayered cell sheets are stacked in layers.…”
Section: Introductionmentioning
confidence: 99%